“MORE VALUEBLE?” PORTFOLIO MIX: ISLAMIC SOCIAL RESPONSIBILITY STOCK - Herwinda Asri Wahyuni; Andewi Rokhmawati; Ahmad Fauzan Fathoni; Ifa Adina Yafiz (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2021)
This research was conducted to analyze the optimal portfolio formation using the Single Index Model method by combining stocks included in the SRI-Kehati Index and listed on the Indonesian Sharia Stock Index (ISSI) with the aim of survival and applying sharia principles then measuring optimal portfolio performance using Sharpe Index, Treynor Index, and Jansen Alpha Index. The object of research used is stocks that are consistently included in the Sri Kehati Index and ISSI for the period December 2018 - December 2019. The results of this study show that the optimal portfolio formed has a higher return compared to the benchmark (IHSG) which is 1.99%, meanwhile, the standard deviation of the portfolio or it can be interpreted as portfolio risk is 1.1%. In performance appraisal, in addition to the Jensen Index, the optimal portfolio formed has better performance than the IHSG.